Modification of barley dietary fiber through chemical treatments in combination with thermal treatment to improve its bioactive properties. Issue 1 (1st January 2018) - Bader Ul Ain, Huma; Saeed, Farhan; Arshad, Muhammad Umair; Ahmad, Nazir; Nasir, Muhammad Adnan; Amir, Rai Muhammad; Kausar, Rukhsana; Niaz, Bushra
ABSTRACT: The present research was carried out to observe the comparative effectiveness of different chemical treatments in combination with simultaneous thermal treatment on soluble (SDF) and insoluble dietary fiber (IDF) ratio to improve functional properties of barley. For this purpose, two varieties of barley, i.e., Haider-93 and Jau-87 were assessed for chemical composition, mineral, non-starch polysaccharides, and dietary fiber contents through respective methods. Two varieties were chemically treated through acid, alkaline, and consecutive acid–alkaline treatments in combination with thermal treatment. Results of chemical composition revealed that Jau-87 was higher in moisture (11.4%), crude fat (2.67%), and crude fiber (4.70%), whereas Haider-93 exhibited higher ash (2.56%) and crude protein content (12.7%). Moreover, barley is a rich source of potassium ranging from 4.77 to 5.07 g/kg. Likewise, main non-starch polysaccharides in barley were arabinoxylan (3.60–3.77%) and beta-glucan (3.65–3.67%). Furthermore, barley contains more IDF (12.00–12.40 g/100 g dm) than SDF (4.73–5.70 g/100 g dm). Additionally, modification of SDF (23.68%) and IDF (11.69%) ratio through acid treatment was nonsignificant, while acid–alkaline treatment showed highly significant results, i.e., 771.46% increased in SDF and 53.39% decreased in IDF. It is concluded that chemical treatments alone or in combination with pressure cooking increased SDF. However, simultaneous effect of acid and alkaline treatment most effectively increased the solubility of barley.